PERKEMBANGAN DAN POLA STRUKTUR EKONOMI SEKTOR PERTANIAN DI KABUPATEN LIMA PULUH KOTA - Syahrial, Syahrial; Hasibuan, Nina Marianna; Leovita, Angelia (MEDIAGRO, 2023)
The agricultural sector is one of the largest contributors to the GRDP of the Fifty Cities District, therefore the Fifty Cities district is able to increase the economic potential of the agricultural sector. This study aims to examine the pattern of economic development in the agricultural sector in Fifty Cities District. This research uses Entropy Diversity Index analysis. The results of the study showed that agricultural output in the Fifty Cities District was not developed/unequal. Commodities, cassava, citrus and rubber were fast growing commodities that dominated the agricultural economic growth in the Fifty Cities District.